Activity Test and Mechanism Study of 3DOM Ce0.8M0.1Zr0.1O2 (M=Cr, Sn, Fe, Co, Ni, Mn, Cu) Catalyst in the Selective Catalytic Reduction of NO by CO. Issue 23 (19th October 2021) - Liu, Xia; Liu, Hao; Li, Danyang; Ning, Gangjie; Li, Xinxin; Dong, Lihui; Li, Bin
Abstract: A series of three‐dimensionally ordered macroporous (3DOM) Ce0.8 M0.1 Zr0.1 O2 (M=Cr, Sn, Fe, Co, Ni, Mn, Cu) catalysts are synthesized and used in CO selective catalytic reduction of NOx . The results show that the NO conversion rate of 3DOM Ce0.8 Cu0.1 Zr0.1 O2 catalyst at a lower temperature (150 °C) is close to 60 %. Besides, 3DOM Ce0.8 Cu0.1 Zr0.1 O2 kept a stable NO removal efficiency within a wide range of gas hourly space velocity (GHSV) and long reaction time and exhibited remarkable resistance to H2 O and SO2 poisoning, both individually and simultaneously. At the same time, the formation of the 3DOM structure not only improves the reduction performance and surface active sites of the catalyst, but also forms more oxygen defects and Ce 3+ in the catalyst due to the strong synergistic effect of metal ions and ceria, which improves the surface oxygen concentration of the composite oxide catalyst and further improves the catalytic activity. In addition, the doping of copper ions on the surface of the 3DOM Cu‐CZ catalyst can improve the activity of the catalyst and it can get trapped by CO to form Cu + ‐CO, which plays an important role in the NO+CO reaction at low temperature. The existence of oxygen vacancy at high temperature is beneficial to the activation of O2 and the dissociation of NO in the process of CO oxidation. The reaction of NO+CO over 3DOM Cu‐CZ catalyst follows L−H and E−R mechanism respectively. Abstract : Composite oxides : The NO conversion rate of a three‐dimensionally ordered mesoporous (3DOM) Ce0.8 Cu0.1 Zr0.1 O2 catalyst at lower temperature (150 °C) is close to 50 %. The catalyst exhibited remarkable resistance to H2 O and SO2 poisoning, both individually and simultaneously. The formation of the 3DOM structure improves the reduction performance and surface active sites of the catalyst. In addition, the reaction of NO and CO over 3DOM Cu‐CZ catalyst follows Langmuir‐Hinshelwood and Eley‐Rideal mechanism, respectively.